1999
DOI: 10.1046/j.1365-3083.1999.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Suppresses the Induction of Nitric Oxide Synthesis in Interferon‐γ‐Treated L929 Fibroblasts

Abstract: The effects of immunosuppressant cyclosporin A (CsA) on nitric oxide (NO) production and inducible NO synthase (iNOS) activity in murine L929 fibroblasts were investigated. IFN-g-induced NO production in L929 cells was mediated through an iNOS-dependent L-arginine-NO pathway, since it was abrogated by a selective inhibitor of iNOS, aminoguanidine. CsA applied simultaneously with IFN-g caused a dose-dependent reduction of NO synthesis in L929 cells. However, CsA did not influence the enzymatic activity of iNOS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The previously reported mechanism of CSA action on T cells involves the inhibition of phosphatase calcineurin (22). However, there is ample evidence suggesting that CSA action is independent of calcineurin in non‐T cells (30, 31). To clarify whether the calcineurin pathway plays a role in CSA‐induced VEGF suppression in FLS, FK‐506, a well‐known calcineurin inhibitor, was tested for its effects on VEGF production.…”
Section: Resultsmentioning
confidence: 99%
“…The previously reported mechanism of CSA action on T cells involves the inhibition of phosphatase calcineurin (22). However, there is ample evidence suggesting that CSA action is independent of calcineurin in non‐T cells (30, 31). To clarify whether the calcineurin pathway plays a role in CSA‐induced VEGF suppression in FLS, FK‐506, a well‐known calcineurin inhibitor, was tested for its effects on VEGF production.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is in agreement with the study of Wimalawansa (2000), which shows that nitric oxide donor, nitroglycerin, reverses the ovariectomy-induced osteopenia. On the other hand it has been suggested that cyclosporin-A suppresses nitric oxide synthesis in L929 cells independent of cacineurin inhibition and interfering with intracellular pathways involved in the nitric oxide synthase induction, rather than inhibiting its enzymatic activity (Trajkovic et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…prevents the activation of other enzymes like the cyclooxigenase that is also related to the inflammatory pathway [70]. Other studies have demonstrated that CsA is also able to inhibit the expression and activation of iNOS, an enzyme related to NO overproduction and inflammation [70,71]. mechanisms, and the neuroprotective action of this drug has already been demonstrated in various models of CNS damage, including cerebral ischemia traumatic brain injury and acute SC injury [17,18,30,31,81,82].…”
Section: Calcineurin-independent Mechanismsmentioning
confidence: 99%
“…Although the beneficial action of CsA upon LP could be in part explained by the inhibitory effect of this drug on immune response, it should be stressed that CsA may also exert this positive effect by inhibiting either the expression or the activity of NOS [70,71]. Previous studies have already demonstrated a significant increase in both the expression [102,103] and activity [104] of NOS isoforms, and NO overproduction plays a key role on tissue destruction.…”
Section: Csa Inhibits the Expression And The Activity Of Nitric Oxidementioning
confidence: 99%